2011
DOI: 10.1088/1468-6996/12/5/055008
|View full text |Cite
|
Sign up to set email alerts
|

β-TCP porous pellets as an orthopaedic drug delivery system: ibuprofen/carrier physicochemical interactions

Abstract: Calcium phosphate bone substitute materials can be loaded with active substances for in situ, targeted drug administration. In this study, porous β-TCP pellets were investigated as an anti-inflammatory drug carrier. Porous β-TCP pellets were impregnated with an ethanolic solution of ibuprofen. The effects of contact time and concentration of ibuprofen solution on drug adsorption were studied. The ibuprofen adsorption equilibrium time was found to be one hour. The adsorption isotherms fitted to the Freundlich m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…The successful delivery of anti-inflammatories using calcium phosphate particles has been demonstrated by numerous authors [36,59]. The delivery of ibuprofen using β-TCP particles was demonstrated by Baradari et al [59]. Ibuprofen was soak-loaded onto the particles, with the ibuprofen molecules diffusing into the pores by capillarity and remaining trapped there after solvent removal.…”
Section: Drug and Therapeutic Factor Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…The successful delivery of anti-inflammatories using calcium phosphate particles has been demonstrated by numerous authors [36,59]. The delivery of ibuprofen using β-TCP particles was demonstrated by Baradari et al [59]. Ibuprofen was soak-loaded onto the particles, with the ibuprofen molecules diffusing into the pores by capillarity and remaining trapped there after solvent removal.…”
Section: Drug and Therapeutic Factor Deliverymentioning
confidence: 99%
“…Ibuprofen was rapidly released from the particles, confirming the weak binding affinity between ibuprofen and β-TCP. No structural or chemical modifications were observed from physiochemical characterisation of the ibuprofen-loaded particles indicating that the binding interactions occur through physisorption processes [59].…”
Section: Drug and Therapeutic Factor Deliverymentioning
confidence: 99%
“…It was reported that the interaction between porous β-TCP pellets and ibuprofen is weak. In vitro tests showed the complete release (100%) of ibuprofen due to Van der Waals forces [ 355 ]. Xiao and co-workers reported that an asymmetric coating formed from hydroxyapatite and gelatin on a Ti6Al4V alloy implant released ibuprofen for a minimum of 30 days.…”
Section: Resultsmentioning
confidence: 99%
“…5a-c). The brown-yellow color was ascribed to β-TCP [25][26][27][28][29][30][31][32] ( Fig. 5b) while the darker was linked to the mixture of NiTi substrate, TiO 2 thin film [32,34] and phosphate groups [25][26][27][28][29][30][31][32] (Fig.…”
Section: Resultsmentioning
confidence: 99%